PARTISIPASI MASYARAKAT DALAM PENGELOLAAN SAMPAH PANTAI TELUK PENYU CILACAP - Karnowati, Nandang Bekti; Jayanti, Esih (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 15 No 2 (2021)DO - 10.24843/EJES.2021.v15.i02.p06, 2021)
The problem of waste is a challenge faced by most countries in the world. The problem of waste will continue if not addressed and will pollute the environment and negatively impact the tourist attraction area. For that, there needs to be real action to overcome the problem of Cilacap Turtle Bay beach waste. The purpose of this study is to find out the influence of variable understanding, will and income on community participation in waste management. Respondents are people who live on the coast of Turtle Bay as many as 100 people. The data was analyzed using Partial Least Square by measuring the outer model and the inner model. The results showed that the variables of understanding, willingness and income positively affect community participation in turtle bay waste management. Government support is the motivation that people expect in sustainable waste management. Keywords: participation; waste management; understanding; willingness; income.